Germinated brown rice and bioactive rich fractions: on going journey from R&D to commercialisation - Ismail, Maznah (Universiti Putra Malaysia Press, 2016)
Over the past few decades, research has indicated a strong relation between nutrition and health. Recent advances in molecular medicine combined with the wealth of information generated by the Human Genome Project have fostered the emergence of nutrigenomics, a powerful new discovery tool that investigates the effects of nutrients and dietary ingredients on gene expression. Nutrigenomics may provide the strategies for the development of safe and effective dietary interventions against chronic diseases such as cardiovascular diseases, cancers, diabetes, Alzheimer’s disease and the obesity epidemic. The increasing realisation that diet interacts with our genome at different levels, to induce changes towards health improvement and disease prevention, has been driving the search for functional foods and bioactive compounds or collectively known as nutraceuticals that promote health. My research has focused on finding those local foods and plant bioresources that can be used to improve the health of Malaysians and world community at large and to unravel their nutrigenomic mechanisms for successful interventions. Since rice is the staple of Malaysians and half of the world population, search on new rice types that can impart health benefits has been one of our research focus. These include work on germinated brown rice which was funded by Bernas and a new specialty high amylose rice partially funded by The World Academy of Sciences (TWAS) both of which have been found to have anti-diabetic property. The desire to maximise the potentials of phytochemicals and food bioactives has led our team to develop “bioactive rich fractions” in which extracts contain multiple bioactive compounds, but with elevated levels of the selected primary or lead compounds. Our bioactive rich fractions have generally proven more effective than single bioactive compounds or even pharmaceutical agents. Moreover, the use of supercritical fluid extraction system as a promising green technology has enabled the extraction and fractionation of bioactive rich fractions. The presence of the multiple bioactive compounds ensures food synergy, in which different bioactives act synergistically to produce superior functional effects in comparison with single bioactive compound or even drugs. Although rich fractions effectively increase the bioactivity of the extract or food, the standardisation and quality assurance process can be challenging, and much of our research is currently focused on these areas. My work on bioactive-rich fractions has contributed in no small measure in advancing the fields of nutraceuticals and nutrigenomics. Furthermore, several successes have been achieved in the field of nanotechnology for the pharmaceutical industry, which has recently been extended to nutraceuticals and functional foods industry. Our experience with nanonisation of nutraceuticals is so far promising in enhancing the bioactivity of nutraceuticals through increased duodenal absorption or tissue uptake and reducing their side effects profile. Despite the successes recorded thus far, commercialising research outputs into commercial products has been challenging. Nevertheless with the strong support from the University and my research team, we have managed to commercialise two nutraceutical products through the setting up of two start-up companies namely Nutracreme Sdn Bhd and Orygold Sdn Bhd in the hope that this will bring benefits to the general populace for better quality of life.